Integration of Biological Networks for Acidithiobacillus thiooxidans Describes a Modular Gene Regulatory Organization of Bioleaching Pathways - Cortés, María Paz; Acuña, Vicente; Travisany, Dante; Siegel, Anne; Maass, Alejandro; Latorre, Mauricio (Frontiers in Molecular Biosciences, 2020)
Acidithiobacillus thiooxidans has positioned itself as one of the most efficient biomining species, highlighting its ability to oxidized reduced inorganic sulfur compounds, coupled with its elevated capacity to tolerate heavy metals. In this work, using an in silico semi-automatic genome scale approach, two biological networks for At. thiooxidans Licanantay were generated: i) An affinity transcriptional regulatory network composed by 42 regulatory family genes and 1501 operons (57% genome coverage) linked through 2646 putative DNA binding sites (arcs), ii) A metabolic network reconstruction made of 523 genes and 1203 reactions (22 pathways related to biomining processes). Through the identification of confident connections between both networks (V-shapes), it was possible to identify a sub-network of transcriptional factors (34 regulators) regulating genes (61 operons) encoding for proteins involved in biomining-related pathways. The network analysis suggests that transcriptional regulation of biomining genes is organized into different modules. The topological parameters showed a high hierarchical organization by levels inside this network (14 layers), highlighting transcription factors CysB, LysR and IHF as complex modules with high degree and high number of controlled pathways. In addition, it was possible to identify transcription factor modules called origons (not controlled by other regulators). Inside this group, the origon CysB is the main module involved in gene regulation of several bioleaching processes. In particular, metabolic processes related to energy metabolism (such as sulfur metabolism) show a complex integrated regulation, where different origons are controlling several genes. In contrast, pathways involved in iron homeostasis and oxidative stress damage are mainly regulated by unique origons, conferring Licanantay an efficient and specific metal resistance response. This study shows new evidence in terms of transcriptional regulation at system level scale broadening the study of bioleaching in At. thiooxidans species.